PENGARUH MOTIVASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA TANGERANG SELATAN - Raisha Fatihah, Abda; Sudarso, Eko (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. To determine the effect of motivation on employee performance, To determine the effect of work discipline on employee performance, To determine the simultaneous effect of work motivation and career development on employee performance at the Regional Disaster Management Agency (BPBD) Office of South Tangerang City. The research method uses quantitative with a population of 87 employees, with a saturated sampling technique, namely the entire population is used as a sample. It can be concluded that the results of the calculation of the t-test value of the Motivation variable (X1) with a t count of 4.779 and a significance of 0.000. Because t count is greater than t table (4.779> 1.988) and the significance is less than 5%, Ha is accepted and H0 is rejected, it can be stated that Motivation (X1) has a significant effect on Employee Performance (Y). It is concluded that the results of the calculation of the t-test value of the Career Development variable (X2) with a t count of 6.634 and a significance of 0.000. Because t count is greater than t table (6.634 > 1.988) and the significance is less than 5% (0.000) then Ha is accepted and H0 is rejected, it can be stated that Career Development (X2) has a significant effect on Employee Performance (Y). The results of the analysis in the table above, namely the ANOVA test, obtained an F count value of 60.984 while F table ( 0.05) for n = 84 was 2.71. So F count > from F table ( 0.05) or 60.984 > 2.71, with a significant level of 0.000 because 0.000 <0.05, it can be said that Motivation (X1), Career Development (X2) and together have an effect on Employee Performance (Y). Keywords: Motivation, Career Development, Employee Performance